2020
DOI: 10.1111/jgs.16783
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Lung Ultrasound Score (PLUS): A New Tool for Detecting Pneumonia in the Oldest Patients

Abstract: OBJECTIVES To compare the diagnostic accuracy of lung ultrasound (LUS) and standard chest X‐ray (CXR) in older patients admitted to an acute‐care geriatric ward for suspected acute pneumonia, and to develop an easy‐to‐use diagnostic tool, now called Pneumonia Lung Ultrasound Score (PLUS), for early risk stratification. DESIGN Prospective, single‐center, cohort study. SETTING Acute‐care geriatric ward of tertiary care center. PARTICIPANTS Individuals, aged 65 years and older, with suspected acute pneumonia. MEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
0
12
0
8
Order By: Relevance
“…In the present observational, single-center study we performed a post-hoc analysis of a cohort of older patients hospitalized for non-COVID-19 pneumonia admitted to our Geriatrics Unit from July 2018 to January 2019 [ 7 ], and data collected from a cohort of older patients consecutively hospitalized for COVID-19 pneumonia from April to March 2020. In both the cohorts, demographic characteristics and clinical history were obtained at admission; Charlson comorbidity index [ 8 ] was reported to evaluate the patients’ burden of comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…In the present observational, single-center study we performed a post-hoc analysis of a cohort of older patients hospitalized for non-COVID-19 pneumonia admitted to our Geriatrics Unit from July 2018 to January 2019 [ 7 ], and data collected from a cohort of older patients consecutively hospitalized for COVID-19 pneumonia from April to March 2020. In both the cohorts, demographic characteristics and clinical history were obtained at admission; Charlson comorbidity index [ 8 ] was reported to evaluate the patients’ burden of comorbidities.…”
Section: Methodsmentioning
confidence: 99%
“…In both studies, the accuracy of LUS combined with PCT was comparable to that obtained in our study combining LUS and C-reactive protein. A recent study performed in an acute Geriatrics Unit demonstrated that adding clinical and biochemical variables (including C-reactive protein) to LUS improved diagnostic accuracy, leading to a more accurate diagnosis of pneumonia in old patients with acute respiratory failure [ 31 ]. Thus, our findings suggests that LUS is a useful tool for the diagnosis of acute pneumonia in CCU and is accuracy improved combining information from serum C reactive protein mainly reducing the number of false positive results and increasing the specificity of the test.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic Ultrasonography also called Pleural and Lung Ultrasonography (PLUS) [ 46 ] is a useful tool to detect causes undelying to dyspnea, especially when standard thoracic radiographic images are uncertain [ 46 ].…”
Section: Ultrasonographymentioning
confidence: 99%